Differential diversifications of South American and Eastern Asian disjunct genera Bocconia and Macleaya (Papaveraceae). Issue 1 (18th October 2017) - Li, Jianhua; Murray, K. Gregory; Li, Pan; Brown, Kenneth
Abstract: Bocconia (10 species) and Macleaya (2 species) are two disjunct genera between South America and eastern Asia (EAS) in the Papaveraceae offering an opportunity to compare its biogeographic history with that of the well‐known disjunction between EAS and eastern North American (ENA). Our phylogenetic analyses of the chloroplast matK and rbcL gene sequences of Ranunculales including two species of Macleaya and six species of Bocconia supported the monophyly of Bocconia, Macleaya, and Chelidonioideae to which Bocconia and Macleaya belong. Nucleotide sequences of matK, rbcL, and nrDNA ITS supported the sister relationship of Bocconia and Macleaya . Biogeographic analyses of Chelidonioideae using S‐DIVA (statistical dispersal vicariance analysis) and DEC (dispersal extinction cladogenesis) methods inferred Eurasia as the most likely ancestral area of Bocconia and Macleaya and suggested no extinction events in either Bocconia or Macleaya . This agrees with the "Out‐of‐Asia" pattern of the EAS‐ENA disjunction. Molecular dating of Ranunculales with fossil‐based calibrations showed that Bocconia and Macleaya diverged in the late Eocene and early Oligocene, which is much earlier than most EAS‐ENA disjunct taxa. The disjunction may have formed via long distance dispersal or boreotropical connections via the North Atlantic and Bering land bridges. Both Bocconia and Macleaya diversified in the late mid‐Miocene, but Bocconia has apparently experienced a greater diversification probably aided by the evolution of the bird dispersal syndrome in fruit and seed after migration to South America. The greater diversification of Bocconia is also evidenced by the diverse leaf morphology and growth habit in response to colonization in various local habitats in South America.